Porous NiCo2O4 nanoarray-integrated binder-free 3D open electrode offers a highly efficient sensing platform for enzyme-free glucose detection. Issue 11 (18th May 2018) - Luo, X.; Huang, M.; He, D.; Wang, M.; Zhang, Y.; Jiang, P.
Abstract : Porous binary metal oxide NiCo2 O4 NWA/CC was prepared and utilized as a 3D binder-free open electrode for enzyme-free sensing with high performance. Abstract : High electrical conductivity and the exposure to more active sites are crucial to boost the performance of a glucose sensor. A porous binary metal oxide nanoarray integrated on a binder-free 3D electrode is expected to offer a highly sensitive sensing platform. As a model, porous NiCo2 O4 nanowire arrays supported on carbon cloth (NiCo2 O4 NWA/CC) have been prepared and used for enzyme-free glucose sensing. NiCo2 O4 NWA/CC shows larger effective surface area, superior electronic conductivity, and higher catalytic activity towards enzyme-free glucose sensing, with a linear range from 1 μM to 0.63 mM, a sensitivity of 4.12 mA mM −1 cm −2, and low detection limit of 0.5 μM. Moreover, NiCo2 O4 NWA/CC also displays good selectivity and stability and thus, it can be reliable for glucose detection in human serum samples. These findings inspire the fabrication of a high-performance electrochemical sensing platform by preparing porous binary metal oxide nanoarrays supported on a 3D conductive substrate.